The Tallgrass Prairie at Fort Riley - Brian Obermeyer (Symphony in the Flint Hills, 2013)
Fort Riley – or Camp Center as it was originally named due to its proximity to the geographic center of the US – was first surveyed in 1852 to serve as a military post to protect traders moving along the Oregon-California and Santa Fe trails.
Keywords: Fort Riley; Tallgrass; prairie; native; nature; grass; plains; military; army; Flint Hills; Camp Center; elk; animals; species; biomass; perennials; forbs; limestone; habitat; ecosystem; niche; insects; birds; bird; lightning; fire; burning; Native Americans; Indians; tradition; trees; invasive; threat; pest